Barriers to the Adoption of Technological Innovations in Corrections: a Review and Case Study - Link, Tanja C. (International journal of offender therapy and comparative criminology, 2021)
Over 600,000 criminal justice involved individuals are released from state and federal prisons each year, and close to 5,000,000 former offenders are placed under some form of community-based supervision. Access to services that may facilitate the reentry process is complicated and more often than not, returning citizens have significant and wide-ranging needs left unaddressed that require a comprehensive approach. In the current paper, we discuss the adoption and implementation processes of technological innovations noted in the criminal justice and correctional literature, as well as other disciplines, while using examples and lessons learned from a pilot project evaluating a new technology known as Pokket, which is a cloud-based service aimed at improving the re-entry process for returning citizens, service providers, and criminal justice agencies.